2017
DOI: 10.14393/bj-v33n4a2017-36709
|View full text |Cite
|
Sign up to set email alerts
|

Performance of organomineral fertilizer in winter and rainy potato crop

Abstract: ABSTRACT:The Agata potato is the most important economic sources of food in Brazil. However, fertilization for this crop has been carried out incorrectly, increasing production costs. Thus, the use of organomineral fertilizer reduces the amount of nutrient applied, facilitates the release of nutrients more slowly and brings improvement in the chemical, physical and biological attributes of the soil. The objective of this work was to evaluate the efficiency of organomineral fertilizers rates and comparate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The results of the application of OMF to the productivity of several species have been reported in the literature (Ferreira et al, 2022;, including potato cultivation with pelleted OMF (Cardoso et al, 2015) and liquid OMF (Souza et al, 2017). Cardoso et al (2017) applied pelleted OMF in planting and observed a 22% higher productivity than mineral fertilizer, which corroborates the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the application of OMF to the productivity of several species have been reported in the literature (Ferreira et al, 2022;, including potato cultivation with pelleted OMF (Cardoso et al, 2015) and liquid OMF (Souza et al, 2017). Cardoso et al (2017) applied pelleted OMF in planting and observed a 22% higher productivity than mineral fertilizer, which corroborates the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The use of BF promoted increases in the production of larger diameter tubes, which increased the value and quality of the final product. Studies have reported increases in productivity and improvements in the quality of tubers from the use of BF applications when compared to the application of only chemical fertilizers for the Atlantic and Agata cultivars (Cardoso et al, 2015;Cardoso et al, 2017). Mohamed et al (2017) found that the productivity of potatoes was 24% greater with green manure than with mineral fertilization, which indicated the potential of alternative fertilizers to provide nitrogen for the growth and development of potato.…”
Section: Productivity and Soluble Solids Contentsmentioning
confidence: 99%
“…In addition, in some situations, weather conditions may also influence the efficiency of the fertilizers. Cardoso et al (2017) did not observe differences between organomineral and inorganic fertilizers for a winter potato ( Solanum tuberosum L.) crop, but for the rainy‐season crop, potato plants fertilized with the organomineral had higher production.…”
mentioning
confidence: 82%